Application of the Dynamic Condylar Screw (DCS)- and Dynamic Hip Screw (DHS) Implant Systems in the Horse - Auer, J. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
The surgical technique for application of the dynamic condylar screw (DCS)- and dynamic hip screw (DHS) implant systems is described and then illustrated by 3 clinical cases. The DCS/DHS system ist stronger and more versatile than the regular DCP or angled blade plate (ABP). This system can be successfully applied for osteotomies and/or fractures of the epiphyseal/metaphyseal region of a longbone in horses. Such fractures are especially difficult to repair because of the small number of implants which can be inserted in the smaller metaphyseal portion of the bone. By using the DCS/DHS system double plating may be unnecessary in selected cases. The combination of the DCS/ DHS system with 5.5 mm diameter cortical bone screws represent ideal implants for internal fixation of longbone fractures and corrective osteotomies in the horse.
Keywords: Dynamic condylar screw (DCS); Dynamic hip screw (DHS); Implant systems; Internal fixation; Longbone fractures; Corrective osteotomies